Effectiveness of Differentiated Learning in Enhancing Social Studies Outcomes among Sixth-Grade Students - Nursanti, Nursanti; Nurpadilah, Nurpadilah; Saimima, Raihana; Latukau, Jubaid (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
Differentiated learning has gained attention as an inclusive instructional strategy that adapts to diverse student needs. This quasi-experimental study aimed to examine the impact of differentiated instruction on Social Studies learning outcomes among sixth-grade students at MIS Persiapan Negeri Namlea. Two groups were involved: an experimental group receiving differentiated instruction and a control group taught using conventional methods. Pre-test and post-test scores were analyzed to determine the effect of the intervention. Normality tests confirmed the appropriateness of parametric analysis, and an independent samples t-test revealed a statistically significant difference in learning outcomes (p = 0.050). The findings suggest that differentiated instruction enhances student performance by allowing tailored content delivery and assessment. While both groups showed improvement, the experimental group demonstrated higher gains, indicating the effectiveness of personalized learning approaches in fostering academic growth. These results support the use of differentiated learning in elementary Social Studies instruction, especially in settings with varied student readiness and learning preferences. Further studies are recommended to explore long-term effects and its implementation across subjects and grade levels.